Pharmacovigilance study in medicine department in a tertiary care hospital - Mishra, Rajat; Jeevangi, Santosh Kumar; Vardhamane, Shrenik; Kumar, Sunil (International Journal of Basic & Clinical Pharmacology, 2016)
Background: Adverse drug reactions (ADRs) are major worldwide public health problem. Proper reporting of an ADR is very important as it reduces number of deaths due to ADR and extra financial burden on patients. The aim of the study was to assess the pattern of ADR reporting in outpatients and inpatients of medicine department and to assess their causality, severity and preventability. Methods: This was a prospective observational study done from April 2013 to June 2014 or in 100 consecutive study subjects (which ever happen first) with ADRs in department of medicine. The clinical pattern, spectrum of ADRs reported and assessment of ADRs in terms of causality, severity and preventability .The causality, severity and preventability assessment was done on the basis of applying various scales for each of them. Results: A total of 153 suspected ADRs were reported and evaluated from 100 patients. Dermatological system (28%) was most commonly involved. Drug class most commonly associated was Antimicrobials (51%). 68% ADRs were classified as “Probable” in view of causality, while 68% were found to be “Moderate” in case of severity. In 65% of the cases the ADRs was “Probably Preventable”. In majority of the cases the suspected drug was withdrawn and alternate therapy was instituted. Most patients recovered from the ADR.70% of these ADR was Type A. Conclusions: Awareness about ADR reporting is still poor amongst healthcare professionals in India. Conducting regular training programmes can improve the number of ADR reporting.